The value of loss of load of Luzon Grid outside of Meralco coverage area - Guinto, Danilo C., Jr (2011)
The cost incurred by customers due to power interruptions represent the economic consequences of supply curtailment when the demand temporarily exceeds the available supply. To quantify these costs, this study used the survey method which is considered as fundamental and methodological approach that has been used to assess customer interruption costs. 1,065 respondents from residential, commercial, and industrial sectors were analyzed to determine the qualitative effects of power interruptions, the variation of the degree of effects of power interruptions, the actions that customers are willing to take during power interruptions, and the monetary costs of power interruptions. A mathematical model for the Value of Loss of Load (VoLL) in the Luzon Grid was also formulated out of the Willingness-to-Pay (WTP) and Willingness-to-Accept (WTA) payment data. The model can be used to establish the optimal level of ancillary services.